2006
DOI: 10.1093/mutage/gel017
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and endoreduplication inducing activity of the food flavouring eugenol

Abstract: Eugenol (1-allyl-3-methoxy-4-hydroxybenzene; CAS No. 97-53-0), a compound extracted from clove oil and marjoram, is widely used as a food flavouring substance and is present in spices such as basil, cinnamon and nutmeg. It is also used in dentistry as an antiseptic and analgesic. Structural similarities with the class IIB IARC carcinogen safrole raises questions on its putative carcinogenicity. We evaluated the genotoxicity of eugenol in V79 cells using chromosomal aberrations (CAs), with and without rat liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 33 publications
1
35
1
1
Order By: Relevance
“…The antibacterial activity of the essential oil may be associated with the high eugenol content, which has been tested previously and was found to have a significant antibiotic activity (Chaieb et al 2007;Zheng et al 1992). Eugenol is also used widely as an analgesic and antiseptic in clinical dentistry (Maralhas et al 2006). Its antibacterial activity against cariogenic bacteria including Streptococcus mutans and Streptococcus salivarius has been reported (Rasheed and Haider 1998).…”
Section: Resultsmentioning
confidence: 97%
“…The antibacterial activity of the essential oil may be associated with the high eugenol content, which has been tested previously and was found to have a significant antibiotic activity (Chaieb et al 2007;Zheng et al 1992). Eugenol is also used widely as an analgesic and antiseptic in clinical dentistry (Maralhas et al 2006). Its antibacterial activity against cariogenic bacteria including Streptococcus mutans and Streptococcus salivarius has been reported (Rasheed and Haider 1998).…”
Section: Resultsmentioning
confidence: 97%
“…We do not know whether these unidentified constituents contributed to some of the toxicity observed. The amount of individual chemicals comprising each batch should be listed since methyleugenol has been reported to be genotoxic (Maralhas et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Its main ingredient EUG functions as an antioxidant (Ogata et al, 2000) and is widely used in the food industry and dentistry as a cement and sedative agent (Markowitz et al, 1992). It has been shown to induce chromosomal aberrations and endoreduplication in vitro (Maralhas et al, 2006). Other research suggests that methyleugenol may cause DNA damage in rat liver (Ding et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of COX-2 gene induced by TA was also abolished by eugenol. Maralhas et al [31] showed that eugenol induces chromosomal aberrations and endo-reduplication in V79 cells, in the absence of an exogenous biotransformation system, suggesting a direct acting genotoxic mechanism, possibly as a topoisomerase II inhibitor. Abraham [32] indicated that eugenol pre-treatment can lead to a moderate reduction in genotoxicity of cyclophosphamide, procarbazine, N-methyl-N'-nitro-N-nitrosoguanidine and urethane.…”
Section: Monoterpenes and Anticarcenogenesis Activitymentioning
confidence: 99%